Stochastic Process in the Concentrating System of a Solar Power Plant for Greenhouse Agriculture - Liu, Jian (International Journal of Multidisciplinary Research, 2026)
Agricultural greenhouses are usually located in the suburbs or remote areas away from towns, and generally speaking, the cost of transmission and power supply is high, and some remote areas do not even have electricity supply. However, traditional greenhouses contain many different electrical equipment and facilities, and a stable power supply is essential for the normal, economical and efficient operation of the greenhouse. Modern agricultural greenhouses also need to be equipped with complete lighting systems, temperature and humidity control systems, ventilation systems, carbon dioxide concentration controlsystems, irrigation sprinkler systems, etc., which are difficult for traditional greenhouses to achievesmoothly. Traditional greenhouses are usually covered with plastic film, which usually needs to be replaced every year, and the discarded plastic film does not meet the requirements of energy conservation and environmental protection. The problem of "thermal insulation" in greenhouses has also been plaguing greenhouse growers. From the perspective of planting cycle, traditional greenhouses are generally onlyplanted twice a year, and the economic benefits are limited.